Simultaneous Triplet Exciton–Phonon and Exciton–Photon Photoluminescence in the Individual Weak Confinement CsPbBr3 Micro/Nanowires - Zhao, Zhuang; Zhong, Manyi; Zhou, Weichang; Peng, Yuehua; Yin, Yanling; Tang, Dongsheng; Zou, Bingsuo (Journal of physical chemistry. C, 2019)
CsPbX3 perovskites have attracted tremendous attention recently due to their excellent optical properties and potential applications. However, this seemingly counterintuitive fact that CsPbX3 perovskites can act as both extraordinary photovoltaic materials and superior emission mediums has not yet been well understood. In this work, the absorption spectrum, temperature-dependent Raman spectra, temperature- and excitation power-dependent steady-state micro-photoluminescence along with the temperature-dependent emission lifetime dynamics were used to characterize systematically the luminescence processes of solution-grown CsPbBr3 micro/nanowires with weak confinement. A dominative in situ triplet exciton emission at 527 nm with strong exciton–phonon coupling and a series of end-facet cavity-related emission bands in the range of 535–580 nm due to robust exciton–photon coupling were observed simultaneously in individual nanowires. The in situ triplet exciton luminescence shows an abnormal blue shift with increasing temperature, while the end-facet emission bands exhibit a red shift. The exciton binding energy and exciton–phonon coupling energy were extracted to be 57 and 66 meV, respectively, confirming the strong exciton–phonon coupling. Our results could provide new insight into the long-standing issue of intrinsic excitonic properties as well as the photophysical process and exciton–phonon/exciton–photon coupling in CsPbBr3 micro/nanostructures, which are critical and helpful to the development of high-performance optoelectronic devices.